Framework for Facilities Management Services Procurement in Public Buildings in Abuja-Nigeria - Sani Momoh; Jennifer Ayegba; Luqman Oyewobi; Calistus Ayegba; Abdulquadri Bilau; Richard Jimoh (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2021)
Deciding what to provide in-house and what to outsource is not always easy, because of the pros and cons of each approach. This study assessed the suitability of outsourcing and in-house routes for procurement of facilities management (FM) services in public buildings in order to develop a framework to assist FM practitioners in making decisions on procurement of FM services in Abuja. Mixed methods research methodology was adopted involving the administration of 122 structured questionnaires and semi-structured interviews with 10 International Facility Management Association (IFMA) members in Abuja-Nigeria. Findings show that the top three factors driving outsourcing of FM services delivery are cost reduction, improved performance standard and improved customer orientation and service. While, the top three factors driving in-house of FM services delivery are improved quality of services, improved performance standard and improved responsiveness and cycle times. This indicates that the framework to procure FM services includes provision of clear policy which should consist of a policy statement, methodology resource mobilisation, government policy regarding the maintenance of the facility mapping of the facility and a means of measuring performance of FM services providers. The developed framework provides a significant understanding that can support decision making on FM services in terms of whether the route to be adopted is either in-house or outsourcing.